Adaptive fractionated stereotactic Gamma Knife radiotherapy of meningioma using integrated stereotactic cone-beam-CT and adaptive re-planning (a-gkFSRT) - Stieler, Florian; Wenz, Frederik; Abo-Madyan, Yasser; Polednik, Martin; Herskind, Carsten; Giordano, Frank Anton; Mai, Sabine (Strahlentherapie und Onkologie, 2016)
Objective: The Gamma Knife Icon (Elekta AB, Stockholm, Sweden) allows frameless stereotactic treatment using a combination of cone beam computer tomography (CBCT), a thermoplastic mask system, and an infrared-based high-definition motion management (HDMM) camera system for patient tracking during treatment. We report on the first patient with meningioma at the left petrous bone treated with adaptive fractionated stereotactic radiotherapy (a-gkFSRT).MethodsThe first patient treated with Gamma Knife Icon at our institute received MR imaging for preplanning before treatment. For each treatment fraction, a daily CBCT was performed to verify the actual scull/tumor position. The system automatically adapted the planned shot positions to the daily position and recalculated the dose distribution (online adaptive planning). During treatment, the HDMM system recorded the intrafractional patient motion. Furthermore, the required times were recorded to define a clinical treatment slot.ResultsTotal treatment time was around 20 min. Patient positioning needed 0.8 min, CBCT positioning plus acquisition 1.65 min, CT data processing and adaptive planning 2.66 min, and treatment 15.6 min. The differences for the five daily CBCTs compared to the reference are for rotation: −0.59 ± 0.49°/0.18 ± 0.20°/0.05 ± 0.36° and for translation: 0.94 ± 0.52 mm/−0.08 ± 0.08 mm/−1.13 ± 0.89 mm. Over all fractions, an intrafractional movement of 0.13 ± 0.04 mm was observed.ConclusionThe Gamma Knife Icon allows combining the accuracy of the stereotactic Gamma Knife system with the flexibility of fractionated treatment with the mask system and CBCT. Furthermore, the Icon system introduces a new online patient tracking system to the clinical routine. The interfractional accuracy of patient positioning was controlled with a thermoplastic mask and CBCT.
Gesehen am 24.06.2019